2011
DOI: 10.1007/s10646-011-0688-z
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant response and metal accumulation in tissues of Iberian green frogs (Pelophylax perezi) inhabiting a deactivated uranium mine

Abstract: Human mining activities tend often to generate greatly impacted areas which remain contaminated for long periods of time, giving rise to extreme habitats. Mining sites are usually characterized for the production of metal rich effluents with very low pH. In this work we analyzed physical and chemical parameters of water from a deactivated uranium mine pond (M) and a reference site (REF) as well as their metal content. Furthermore, we determined and compared metal accumulation in liver, kidney, bones, muscle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 52 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…The samples were sampled to plastic bottles and acidified with nitric acid Pro Analysis MERCK® (65%) to a pH bellow 2, to prevent metal adsorption, according to the protocol described by Marques et al . 25 , to then be analysed, at the laboratory, to quantify copper concentrations. The tissues were dried at 105 °C by about 24 hours and then weighted and digested in closed falcon tubes with 3 ml HNO 3 (Pro Analysis MERCK®, 65%), at 60 °C, on the oven, by about 8 hours to copper quantification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were sampled to plastic bottles and acidified with nitric acid Pro Analysis MERCK® (65%) to a pH bellow 2, to prevent metal adsorption, according to the protocol described by Marques et al . 25 , to then be analysed, at the laboratory, to quantify copper concentrations. The tissues were dried at 105 °C by about 24 hours and then weighted and digested in closed falcon tubes with 3 ml HNO 3 (Pro Analysis MERCK®, 65%), at 60 °C, on the oven, by about 8 hours to copper quantification.…”
Section: Methodsmentioning
confidence: 99%
“…The volume was completed to 5 ml per sample with Milli-Q® water (18.2 ῼ), according to Marques et al . 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Wood frog tadpoles accumulated whole-body Ni with increasing aqueous Ni concentration. Few researchers examined accumulation of Ni by amphibians in controlled experiments; they rather documented the concentration of Ni in amphibians from contaminated sites in situ that indicated that several amphibian species can accumulate Ni from contaminated sites (Sparling and Lowe 1996;Venne et al 2006;Sohani and Samant 2010;Marques et al 2011;Taiwo et al 2014). In our study, the whole-body Ni concentration never came into equilibrium with the exposure environment based on the log-linear uptake relationship (Figure 1) and BCF values (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Schuytema and Nebeker (1999) analyzed the growth and death of amphibian species Rana aurora exposed to ammonium nitrate and sodium nitrate and tadpoles of the species Xenopus laevis and Pseudacris regilla exposed to urea. Marques et al (2011) studied the contamination of amphibian species Pelophylax perezi in an uranium mine and a non-anthropic reference site and found that some elements may be up to 1000 times more concentrated in mining areas. Nations et al (2011) evaluated the acute effects of ZnO, TiO 2 , Fe 2 O 3 , and CuO in Xenopus laevis and demonstrated that at trace concentrations these compounds were not harmful to the organisms studied.…”
Section: Introductionmentioning
confidence: 99%